REVIVALISME MASYARAKAT ADAT DALAM POLITIK LOKAL DI INDONESIA PASCA-SOEHARTO: STUDI KASUS KOMUNITAS KAMPUNG NAGA, TASIKMALAYA, JAWA BARAT - Mudzakkir, Amin (Jurnal Masyarakat dan Budaya, 2011)
Indigenous people is an important issue in the post-Suharto Indonesian politics. In the struggle over state power and capital, the discourse is used by both human rights activists and indigenous communities as their agenda. The process is described as “adat revivalism”. However, the 'indigenous' term was actually created from a certain social and intellectual process; which shall not taken for granted. In this term, the discourses of indigenous peoples become complexand dynamic. Based on that perspective, this article observes how Kampung Naga traditional community in Tasikmalaya, West Java, deals with government policy on tourism. Through the process of resistance and negotiations, it created a consensus among the community of Kampung Naga and the government.Keywords: Indigenous peoples, revivalism, on tourism policy, Kampung Naga